Li2TiO3 tritium breeder ceramic with mesoporous grain boundary structure and preparation method of Li2TiO3 tritium breeder ceramic
The mesoporous grain boundary structure of Li2TiO3 tritium proliferator ceramics is regulated through flash firing process, which solves the problem of low tritium release efficiency of existing Li2TiO3 tritium proliferator, and achieves the improvement of efficient tritium release and radiation resistance.
Patent Information
- Application Number
- CN202411558066.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing Li2TiO3 tritium proliferator has low tritium release efficiency and cannot meet the self-sustaining engineering design requirements of tritium.
By regulating the flash burning technical parameters, the precise control of the mesoporous pore size and pore density in the Li2TiO3 tritium proliferator ceramic materials is achieved. The flash burning process is used to form a ceramic material with a mesoporous grain boundary structure, which improves the desorption and diffusion of tritium rate.
It improves the tritium release efficiency of tritium proliferator, reduces lithium volatility, ensures high lithium density, and enhances radiation resistance.
Smart Images

Figure CN119241227A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nuclear materials and relates to a Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure and a preparation method thereof. Background Art
[0002] Nuclear fusion energy has the advantages of being clean, safe, and sustainable. However, tritium, one of the reaction fuels, is a radioactive isotope of hydrogen that is almost non-existent in nature. It is generally achieved through the reaction of neutrons and lithium ceramics to achieve "tritium self-sustaining". As a major candidate material for tritium breeders, lithium ceramics have the following advantages: good chemical stability, good compatibility with structural materials, and no magnetohydrodynamic effect. Among the many lithium ceramic tritium breeders, lithium titanate (Li2TiO3) has a moderate lithium density, low tritium release temperature, and excellent mechanical properties. It is selected as the preferred tritium breeder by the International Thermonuclear Experimental Reactor (ITER) and the China Fusion Engineering Test Reactor (CFETR).
[0003] The tritium proliferation process mainly includes the generation and diffusion of tritium in grains, the adsorption and desorption of tritium at grain boundaries, and the diffusion of tritium at interfaces or pores. Among them, the diffusion of tritium at interfaces or pores, as the last link of tritium release, plays a decisive role in whether tritium can be successfully extracted. However, studies have shown that the tritium proliferation efficiency of lithium ceramics is low, far from meeting the engineering design requirements of tritium self-sustaining. It is imperative to improve the efficiency of tritium production and release of tritium breeders. Summary of the invention
[0004] The purpose of the present invention is to provide a Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure and a preparation method thereof, so as to solve the problem of low tritium release efficiency of the existing Li2TiO3 tritium breeder. The present invention is based on flash burning technology, and by adjusting the flash burning technical parameters, the pore size and pore density of the grain boundary mesopores in the Li2TiO3 tritium breeder ceramic material can be precisely controlled, thereby achieving efficient tritium release of the Li2TiO3 tritium breeder.
[0005] The present invention can be implemented by the following technical scheme: providing a method for preparing a Li2TiO3 tritium breeder ceramic having a mesoporous grain boundary structure, comprising:
[0006] (1) preparing Li2TiO3 powder;
[0007] (2) Preparing a Li2TiO3 green billet: placing the Li2TiO3 powder in a mold, placing the mold in a tablet press, and performing compression molding, and demolding to obtain a Li2TiO3 green billet;
[0008] (3) Preparation of Li2TiO3 tritium breeder ceramics: drilling holes at the middle positions of both ends of the Li2TiO3 blank, measuring the distance between the two holes and the width and height of the middle position of the Li2TiO3 blank, and calculating the cross-sectional area of the Li2TiO3 blank;
[0009] Then apply silver paste on the inner wall and surrounding of the holes at both ends of the Li2TiO3 blank;
[0010] Then, two platinum wire electrodes in a box furnace are passed through the holes at both ends of the Li2TiO3 blank and fixed, and the furnace door is closed;
[0011] The furnace temperature and flash firing parameters are set according to the distance between the two holes and the cross-sectional area of the Li2TiO3 blank. After the furnace temperature stabilizes, the Li2TiO3 blank is flash fired. After the flash firing is completed, the power is turned off and the blank is cooled with the furnace to obtain Li2TiO3 tritium breeder ceramics. The flash firing parameters include electric field strength, current density and flash firing time.
[0012] The beneficial effects of adopting the above technical scheme are as follows: the present invention first synthesizes and screens out Li2TiO3 ultrafine powder by a low-temperature solid phase method, then places a mold filled with Li2TiO3 ultrafine powder in a tablet press to press out a Li2TiO3 green billet, and finally sinters the green billet through a flash firing device to obtain a high-tritium-release Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure.
[0013] The present invention combines the superplastic deformation, i.e., the dislocation stacking effect, during the flash sintering process to modify the Li2TiO3 grain boundaries, thereby obtaining a new Li2TiO3 tritium breeder with rich mesoporous grain boundaries. The tritium desorption and diffusion rates of the tritium breeder are improved by increasing the proportion of interfaces or pores. The present invention will provide a theoretical and experimental basis for the structural design of new ceramic tritium breeders.
[0014] Flash sintering is generally a new sintering process that applies a DC or AC electric field to the sample through a wire, increases the field strength during the sintering temperature rise process, and instantly densifies the material when the field strength and temperature critical values are reached. It has the characteristics of low sintering temperature and fast sintering speed. Compared with traditional sintering processes such as atmospheric pressure sintering, hot pressing sintering, and spark plasma sintering, flash sintering only needs to be completed at a relatively low temperature in a short time, with high sintering efficiency and energy saving and environmental protection; most importantly, due to the fast sintering speed, flash sintering can cause superplastic deformation of the sample, forming high-density stacking defects, and then producing abundant nano-mesoporous grain boundaries, which helps to accelerate the diffusion of tritium.
[0015] In a specific embodiment of the present invention, the following steps are also included: the preparation process of the Li2TiO3 powder includes:
[0016] (11) LiOH·H2O and TiO(OH)2 are placed in a ball mill containing a plurality of agate balls, ball milling media is added, and the ball mill is sealed;
[0017] (12) placing the sealed ball mill jar in a planetary ball mill for ball milling to obtain a slurry;
[0018] (13) subjecting the ball-milled slurry to rotary drying to obtain a mixed powder;
[0019] (14) The mixed powder is placed in a crucible, placed in a box furnace, and pre-fired in an air atmosphere; and then ground and sieved to obtain Li2TiO3 powder.
[0020] In a specific embodiment of the present invention, in the step (11), the molar ratio of LiOH·H2O to TiO(OH)2 is 2:1; and the diameter of the agate ball is 2-5 mm.
[0021] In a specific embodiment of the present invention, in the step (11), the ball milling medium is anhydrous ethanol.
[0022] In a specific embodiment of the present invention, in the step (12), the ball milling speed is 200-300 r / min, and the ball milling time is 6-8 h.
[0023] In a specific embodiment of the present invention, in the step (13), the rotary evaporation temperature is 40-60°C, and the rotary evaporation time is 2-4h.
[0024] In a specific embodiment of the present invention, in the step (14), the pre-sintering temperature of the mixed powder is 500-600°C, the pre-sintering time is 2-4h; and the heating rate is 5°C / min.
[0025] In a specific embodiment of the present invention, in the step (14), the mesh size of the sieve used for sieving is 80-120 meshes.
[0026] In a specific embodiment of the present invention, in the step (2), the mold is a dog-bone-shaped mold, and the obtained Li2TiO3 blank is a dog-bone-shaped blank.
[0027] In a specific embodiment of the present invention, in the step (2), during the compression molding process, the molding pressure is 2.5-3.5 MPa, and the holding time is 1-1.5 min.
[0028] In a specific embodiment of the present invention, in step (3), the diameter of the holes punched in the middle of both ends of the Li2TiO3 blank is 0.8-1.2 mm.
[0029] In a specific embodiment of the present invention, in step (3), the furnace temperature is 600-800°C, and the furnace temperature generally reaches stability after a holding time of 1-2 hours; the electric field strength is 70-100 V / cm, and the current density is 40-80 mA / mm 2 , the flash burning time is 10-30s; during the flash burning process, first raise the furnace temperature to 600-800℃, then keep it warm for 1-2h, and start flash burning after the furnace temperature stabilizes.
[0030] The present invention also provides Li2TiO3 tritium breeder ceramics with a mesoporous grain boundary structure prepared by the above method.
[0031] Compared with the prior art, the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure and the preparation method thereof provided by the present invention have the following beneficial effects:
[0032] (1) The present invention uses precursor powder tableting to obtain a dog-bone-shaped green blank, which is then formed using a flash sintering process; compared with the traditional sintering method, the lithium volatilization caused by continuous high-temperature heating is reduced, ensuring a higher lithium density of the proliferation agent;
[0033] (2) The present invention adopts a flash sintering process to obtain a "annual ring"-shaped grain boundary structure, which increases the specific surface area of the grain boundary, enriches the diffusion channel of tritium, and improves the tritium release efficiency;
[0034] (3) The "annual ring"-like grain boundary structure of the tritium breeder lithium titanate ceramic prepared by the present invention is beneficial to reducing the number of irradiated voids, hindering the accumulation of interstitial atoms and the formation of helium bubble clusters, improving the vacancy-interstitial atom recombination efficiency, and effectively improving its radiation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the dog-bone-shaped Li2TiO3 blank prepared by the present invention;
[0036] Figure 2 The XRD spectrum of the Li2TiO3 ceramic prepared by flash sintering in Example 1 of the present invention;
[0037] Figure 3 The SEM test results of Li2TiO3 ceramics prepared in the comparative example and Example 1 of the present invention; (a) SEM image of Li2TiO3 ceramics obtained by sintering in a conventional box furnace; (b) SEM image of Li2TiO3 ceramics prepared by flash sintering in Example 1;
[0038] Figure 4 This is a high-magnification SEM image of the Li2TiO3 ceramic prepared by flash sintering in Example 1 of the present invention; wherein (b) is an enlarged schematic diagram of the dotted frame portion in (a);
[0039] Figure 5SEM images (5×10 4 (a) 630℃-40mA / mm 2 ; (b) 630℃-60mA / mm 2 ; (c) 630℃-80mA / mm 2 ; (d) 680℃-60mA / mm 2 ; (e) 730℃-60mA / mm 2 ;
[0040] Figure 6 SEM images (5×10 3 (a) 630℃-40mA / mm 2 ; (b) 630℃-60mA / mm 2 ; (c) 630℃-80mA / mm 2 ; (d) 680℃-60mA / mm 2 ; (e) 730℃-60mA / mm 2 .
[0041] Figure 7 The H2 desorption peak area of Li2TiO3 ceramics prepared under different flash firing conditions in Examples 1-5 of the present invention; wherein, (a) gives the H2 desorption peak area of Li2TiO3 ceramics at different flash firing current densities; (b) gives the H2 desorption peak area of Li2TiO3 ceramics at different flash firing furnace temperatures. DETAILED DESCRIPTION
[0042] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0043] The preparation method of the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure provided by the present invention mainly comprises:
[0044] The low-temperature solid-phase method is used to synthesize ultrafine Li2TiO3 powder: a certain amount of LiOH·H2O and TiO(OH)2 are weighed and placed in a ball mill containing a certain number of agate balls, and then a proper amount of ball milling medium (anhydrous ethanol, solid-liquid mass ratio of 1:6-1:8) is added to the ball mill, and then the suspension after ball milling is placed in a rotary evaporator for drying, and finally the precursor powder is obtained by screening, and the precursor powder is calcined in a box furnace to obtain ultrafine Li2TiO3 powder;
[0045] Dog-bone-shaped Li2TiO3 green billet molding: weigh a certain mass of Li2TiO3 ultrafine powder and put it into a dog-bone-shaped mold. After compaction, place the mold in a tablet press to form it. Apply a certain pressure to the sample, keep the pressure for a period of time, and then demold to obtain a dog-bone-shaped Li2TiO3 green billet (such as Figure 1 shown);
[0046] Preparation of Li2TiO3 ceramics with mesoporous grain boundary structure by flash firing: Use a punch to punch holes in the middle of both ends of the blank, use a vernier caliper to measure and record the distance between the two holes, then measure the width and height of the middle of the blank, set the voltage and current based on the calculation results of the distance between the two holes and the cross-sectional area; then apply silver paste around the hole and its inner wall to increase its conductivity; finally, use two platinum wire electrodes in a box furnace to pass through the holes at both ends of the blank and fix them, close the furnace door, set the program on the panel interface (heating rate, holding time and other related parameters), then start the flash firing program, turn off the power after flash firing for a period of time, cool with the furnace, and take out the Li2TiO3 ceramics.
[0047] The preparation method of the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure provided by the present invention is explained and verified in detail below in combination with comparative examples and embodiments.
[0048] The names, equipment models and manufacturers of the experimental equipment used in the following comparative examples and embodiments are shown in Table 1.
[0049] Table 1 Main instruments and equipment
[0050]
[0051]
[0052] The purity of the raw material LiOH·H2O used in the following comparative examples and examples is 99%, and the purity of the raw material TiO(OH)2 is 98%.
[0053] Comparative Example
[0054] The steps of the preparation method of the Li2TiO3 tritium breeder ceramic provided in this comparative example are as follows:
[0055] (1) preparing Li2TiO3 powder; this step comprises the following sub-steps:
[0056] (11) Weighing raw materials: LiOH·H2O and TiO(OH)2 are weighed according to a molar ratio of 2:1, and anhydrous ethanol 6 times the mass of the raw materials of LiOH·H2O and TiO(OH)2 is added to mix them thoroughly. Then, the mixture is placed in a ball mill that has been cleaned with alcohol and dried. A number of 5 mm agate balls and a number of 2 mm agate balls that have been cleaned with alcohol are added to the ball mill, and the ball mill is sealed with plastic wrap;
[0057] (12) Planetary ball milling: Place the sealed ball mill jar into the planetary ball mill, then fix the ball mill jar in the planetary ball mill, set the ball milling speed to 300 r / min, the ball milling time to 8 h, and take out the slurry after the ball milling is completed;
[0058] (13) Rotary evaporation: Pour the ball-milled slurry into a rotary evaporation bottle through a funnel, fix the rotary evaporation bottle on a rotary evaporator, set the rotary evaporation temperature to 50°C, the rotary evaporation time to 2 h, and take out the mixed powder after the rotary evaporation is completed;
[0059] (14) Pre-calcination: The mixed powder after rotary evaporation is placed in a crucible, placed in a box furnace, and pre-calcined in an air atmosphere; the pre-calcination conditions are: from room temperature to 500°C, the heating rate is 5°C / min, the holding time is 4h, and after the program is completed, the furnace is cooled to obtain Li2TiO3 powder; the obtained Li2TiO3 powder is placed in a mortar and ground, and then passed through a 100-mesh sieve, and then dried and stored;
[0060] (2) Preparation of Li2TiO3 green billet
[0061] Weigh 1.5g of Li2TiO3 powder and put it into a cylindrical mold, place it in a tablet press, and press it into shape. The pressing pressure is 3MPa, and the holding time is 1min. Then demold it to obtain a Li2TiO3 green pellet with a diameter of 20mm.
[0062] (3) Preparation of Li2TiO3 tritium breeder ceramics
[0063] The green blank disc is placed in a crucible of a box furnace for sintering; the sintering conditions are: from room temperature to 500°C, the heating rate is 10°C / min, then from 500°C to 800°C, the heating rate is 5°C / min, and then kept at 800°C for 4 hours; then the temperature is reduced from 800°C to 500°C, the cooling rate is 5°C / min, and the furnace is cooled after 500°C to obtain Li2TiO3 tritium breeder ceramics.
[0064] Example 1
[0065] The steps of the preparation method of the Li2TiO3 tritium breeder ceramic provided in this embodiment are as follows:
[0066] (1) preparing Li2TiO3 powder; this step comprises the following sub-steps:
[0067] (11) Weighing raw materials: LiOH·H2O and TiO(OH)2 are weighed according to a molar ratio of 2:1, and anhydrous ethanol 6 times the mass of the raw materials of LiOH·H2O and TiO(OH)2 is added to mix them thoroughly. Then, the mixture is placed in a ball mill that has been cleaned with alcohol and dried. A number of 5 mm agate balls and a number of 2 mm agate balls that have been cleaned with alcohol are added to the ball mill, and the ball mill is sealed with plastic wrap;
[0068] (12) Planetary ball milling: Place the sealed ball mill jar into the planetary ball mill, then fix the ball mill jar in the planetary ball mill, set the ball milling speed to 300 r / min, the ball milling time to 8 h, and take out the slurry after the ball milling is completed;
[0069] (13) Rotary evaporation: Pour the ball-milled slurry into a rotary evaporation bottle through a funnel, fix the rotary evaporation bottle on a rotary evaporator, set the rotary evaporation temperature to 50°C, the rotary evaporation time to 2 h, and take out the mixed powder after the rotary evaporation is completed;
[0070] (14) Pre-calcination: The mixed powder after rotary evaporation is placed in a crucible, placed in a box furnace, and pre-calcined in an air atmosphere; the pre-calcination conditions are: from room temperature to 500°C, the heating rate is 5°C / min, the holding time is 4h, and after the program is completed, the furnace is cooled to obtain Li2TiO3 powder; the obtained Li2TiO3 powder is placed in a mortar and ground, and then passed through a 100-mesh sieve, and then dried and stored;
[0071] (2) Preparation of Li2TiO3 green billet
[0072] Weigh 0.5g of Li2TiO3 powder and put it into a dog-bone-shaped mold, place it in a tablet press, and press it into shape at a pressure of 2.88MPa for 1min. Then demold it to obtain a dog-bone-shaped Li2TiO3 green billet.
[0073] (3) preparing Li2TiO3 tritium breeder ceramics, which comprises the following sub-steps:
[0074] (31) Punching measurement: Use a punch to punch a hole with a diameter of 1 mm in the middle of both ends of the dog-bone blank. Use a vernier caliper to measure the distance between the two holes and record it. Then continue to measure the width and height of the middle position of the dog-bone blank to obtain the blank size A1 (20.15 mm × 3.34 mm × 1.80 mm). Then calculate the blank cross-sectional area.
[0075] (32) Applying silver paste: Apply silver paste on the inner wall and surrounding of the holes at both ends of the blank to increase its conductivity;
[0076] (33) Flash firing: Use two platinum wire electrodes in a box furnace to pass through the holes at both ends of the dog bone blank and fix them, and close the furnace door; then set the program on the power interface, set the furnace temperature to 630°C, the electric field strength to 80 V / cm, and the current density to 40 mA / mm 2 The flash firing time was 30s, the heating rate was 6℃ / min, and the holding time was 2h. After the furnace temperature stabilized, the flash firing program was started. After the flash firing was completed, the power was turned off and the furnace was cooled to room temperature to obtain dog-bone-shaped Li2TiO3 ceramics.
[0077] Example 2
[0078] The steps of the preparation method of the Li2TiO3 tritium breeder ceramic provided in this embodiment are as follows:
[0079] (1) preparing Li2TiO3 powder; this step comprises the following sub-steps:
[0080] (11) Weighing raw materials: LiOH·H2O and TiO(OH)2 are weighed according to a molar ratio of 2:1, and anhydrous ethanol 7 times the mass of the raw materials of LiOH·H2O and TiO(OH)2 is added to fully mix them. Then, the mixture is placed in a ball mill that has been cleaned with alcohol and dried. A number of 5 mm agate balls and a number of 2 mm agate balls that have been cleaned with alcohol are added to the ball mill, and the ball mill is sealed with plastic wrap;
[0081] (12) Planetary ball milling: Place the sealed ball mill jar into the planetary ball mill, then fix the ball mill jar in the planetary ball mill, set the ball milling speed to 300 r / min, the ball milling time to 8 h, and take out the slurry after the ball milling is completed;
[0082] (13) Rotary evaporation: Pour the ball-milled slurry into a rotary evaporation bottle through a funnel, fix the rotary evaporation bottle on a rotary evaporator, set the rotary evaporation temperature to 50°C, the rotary evaporation time to 2 h, and take out the mixed powder after the rotary evaporation is completed;
[0083] (14) Pre-calcination: The mixed powder after rotary evaporation is placed in a crucible, placed in a box furnace, and pre-calcined in an air atmosphere; the pre-calcination conditions are: from room temperature to 500°C, the heating rate is 5°C / min, the holding time is 4h, and after the program is completed, the furnace is cooled to obtain Li2TiO3 powder; the obtained Li2TiO3 powder is placed in a mortar and ground, and then passed through a 100-mesh sieve, and then dried and stored;
[0084] (2) Preparation of Li2TiO3 green billet
[0085] Weigh 0.5g of Li2TiO3 powder and put it into a dog-bone-shaped mold, place it in a tablet press, and press it into shape at a pressure of 2.88MPa for 1min. Then demold it to obtain a dog-bone-shaped Li2TiO3 green billet.
[0086] (3) preparing Li2TiO3 tritium breeder ceramics, which comprises the following sub-steps:
[0087] (31) Punching measurement: Use a punch to punch a hole with a diameter of 1 mm in the middle of both ends of the dog-bone blank. Use a vernier caliper to measure the distance between the two holes and record it. Then continue to measure the width and height of the middle position of the dog-bone blank to obtain the blank size A2 (18.98 mm × 3.37 mm × 1.81 mm). Then calculate the blank cross-sectional area.
[0088] (32) Applying silver paste: Apply silver paste on the inner wall and surrounding of the holes at both ends of the blank to increase its conductivity;
[0089] (33) Flash firing: Use two platinum wire electrodes in a box furnace to pass through the holes at both ends of the dog bone blank and fix them, and close the furnace door; then set the program on the power interface, set the furnace temperature to 630°C, the electric field strength to 80V / cm, and the current density to 60mA / mm 2 The flash firing time was 30s, the heating rate was 6℃ / min, and the holding time was 2h. After the furnace temperature stabilized, the flash firing program was started. After the flash firing was completed, the power was turned off and the furnace was cooled to room temperature to obtain dog-bone-shaped Li2TiO3 ceramics.
[0090] Example 3
[0091] The steps of the preparation method of the Li2TiO3 tritium breeder ceramic provided in this embodiment are as follows:
[0092] (1) preparing Li2TiO3 powder; this step comprises the following sub-steps:
[0093] (11) Weighing raw materials: LiOH·H2O and TiO(OH)2 are weighed according to a molar ratio of 2:1, and anhydrous ethanol in an amount of 8 times the mass of the raw materials of LiOH·H2O and TiO(OH)2 is added to mix them thoroughly. The mixture is then placed in a ball mill that has been cleaned with alcohol and dried. A number of 5 mm agate balls and a number of 2 mm agate balls that have been cleaned with alcohol are added to the ball mill, and the ball mill is sealed with plastic wrap;
[0094] (12) Planetary ball milling: Place the sealed ball mill jar into the planetary ball mill, then fix the ball mill jar in the planetary ball mill, set the ball milling speed to 300 r / min, the ball milling time to 8 h, and take out the slurry after the ball milling is completed;
[0095] (13) Rotary evaporation: Pour the ball-milled slurry into a rotary evaporation bottle through a funnel, fix the rotary evaporation bottle on a rotary evaporator, set the rotary evaporation temperature to 50°C, the rotary evaporation time to 2 h, and take out the mixed powder after the rotary evaporation is completed;
[0096] (14) Pre-calcination: The mixed powder after rotary evaporation is placed in a crucible, placed in a box furnace, and pre-calcined in an air atmosphere; the pre-calcination conditions are: from room temperature to 500°C, the heating rate is 5°C / min, the holding time is 4h, and after the program is completed, the furnace is cooled to obtain Li2TiO3 powder; the obtained Li2TiO3 powder is placed in a mortar and ground, and then passed through a 100-mesh sieve, and then dried and stored;
[0097] (2) Preparation of Li2TiO3 green billet
[0098] Weigh 0.5g of Li2TiO3 powder and put it into a dog-bone-shaped mold, place it in a tablet press, and press it into shape at a pressure of 2.88MPa for 1min. Then demold it to obtain a dog-bone-shaped Li2TiO3 green billet.
[0099] (3) preparing Li2TiO3 tritium breeder ceramics, which comprises the following sub-steps:
[0100] (31) Punching measurement: Use a punch to punch a hole with a diameter of 1 mm in the middle of both ends of the dog-bone blank. Use a vernier caliper to measure the distance between the two holes and record it. Then continue to measure the width and height of the middle position of the dog-bone blank to obtain the blank size of A3 (18.97 mm × 3.37 mm × 1.78 mm). Then calculate the blank cross-sectional area.
[0101] (32) Applying silver paste: Apply silver paste on the inner wall and surrounding of the holes at both ends of the blank to increase its conductivity;
[0102] (33) Flash firing: Use two platinum wire electrodes in a box furnace to pass through the holes at both ends of the dog bone blank and fix them, and close the furnace door; then set the program on the power interface, set the furnace temperature to 630°C, the electric field strength to 80 V / cm, and the current density to 80 mA / mm 2 The flash firing time was 30s, the heating rate was 6℃ / min, and the holding time was 2h. After the furnace temperature stabilized, the flash firing program was started. After the flash firing was completed, the power was turned off and the furnace was cooled to room temperature to obtain dog-bone-shaped Li2TiO3 ceramics.
[0103] Example 4
[0104] The steps of the preparation method of the Li2TiO3 tritium breeder ceramic provided in this embodiment are as follows:
[0105] (1) preparing Li2TiO3 powder; this step comprises the following sub-steps:
[0106] (11) Weighing raw materials: LiOH·H2O and TiO(OH)2 are weighed according to a molar ratio of 2:1, and anhydrous ethanol 7 times the mass of the raw materials of LiOH·H2O and TiO(OH)2 is added to fully mix them. Then, the mixture is placed in a ball mill that has been cleaned with alcohol and dried. A number of 5 mm agate balls and a number of 2 mm agate balls that have been cleaned with alcohol are added to the ball mill, and the ball mill is sealed with plastic wrap;
[0107] (12) Planetary ball milling: Place the sealed ball mill jar into the planetary ball mill, then fix the ball mill jar in the planetary ball mill, set the ball milling speed to 300 r / min, the ball milling time to 8 h, and take out the slurry after the ball milling is completed;
[0108] (13) Rotary evaporation: Pour the ball-milled solution into a rotary evaporation bottle through a funnel, fix the rotary evaporation bottle on a rotary evaporator, set the rotary evaporation temperature to 50°C, the rotary evaporation time to 2 h, and take out the mixed powder after the rotary evaporation is completed;
[0109] (14) Pre-calcination: The mixed powder after rotary evaporation is placed in a crucible, placed in a box furnace, and pre-calcined in an air atmosphere; the pre-calcination conditions are: from room temperature to 500°C, the heating rate is 5°C / min, the holding time is 4h, and after the program is completed, the furnace is cooled to obtain Li2TiO3 powder; the obtained Li2TiO3 powder is placed in a mortar and ground, and then passed through a 100-mesh sieve, and then dried and stored;
[0110] (2) Preparation of Li2TiO3 green billet
[0111] Weigh 0.5g of Li2TiO3 powder and put it into a dog-bone-shaped mold, place it in a tablet press, and press it into shape at a pressure of 2.88MPa for 1min. Then demold it to obtain a dog-bone-shaped Li2TiO3 green billet.
[0112] (3) preparing Li2TiO3 tritium breeder ceramics, which comprises the following sub-steps:
[0113] (31) Punching measurement: Use a punch to punch a hole with a diameter of 1 mm in the middle of both ends of the dog-bone blank. Use a vernier caliper to measure the distance between the two holes and record it. Then continue to measure the width and height of the middle position of the dog-bone blank to obtain the blank size of A4 (17.70 mm × 3.38 mm × 1.76 mm). Then calculate the blank cross-sectional area.
[0114] (32) Applying silver paste: Apply silver paste on the inner wall and surrounding of the holes at both ends of the blank to increase its conductivity;
[0115] (33) Flash firing: Use two platinum wire electrodes in a box furnace to pass through the holes at both ends of the dog bone blank and fix them, and close the furnace door; then set the program on the power interface, set the furnace temperature to 680°C, the electric field strength to 80V / cm, and the current density to 60mA / mm 2 The flash burning time is 30s, the heating rate is 6℃ / min, and the holding time is 2h. After the furnace temperature stabilizes, the flash burning program is started, and after the flash burning is completed, the power is turned off and the furnace is cooled to room temperature to obtain dog-bone-shaped lithium titanate ceramics.
[0116] Example 5
[0117] The steps of the preparation method of the Li2TiO3 tritium breeder ceramic provided in this embodiment are as follows:
[0118] (1) preparing Li2TiO3 powder; this step comprises the following sub-steps:
[0119] (11) Weighing raw materials: LiOH·H2O and TiO(OH)2 are weighed according to a molar ratio of 2:1, and anhydrous ethanol 6 times the mass of the raw materials of LiOH·H2O and TiO(OH)2 is added to mix them thoroughly. Then, the mixture is placed in a ball mill that has been cleaned with alcohol and dried. A number of 5 mm agate balls and a number of 2 mm agate balls that have been cleaned with alcohol are added to the ball mill, and the ball mill is sealed with plastic wrap;
[0120] (12) Planetary ball milling: Place the sealed ball mill jar into the planetary ball mill, then fix the ball mill jar in the planetary ball mill, set the ball milling speed to 300 r / min, the ball milling time to 8 h, and take out the slurry after the ball milling is completed;
[0121] (13) Rotary evaporation: Pour the ball-milled solution into a rotary evaporation bottle through a funnel, fix the rotary evaporation bottle on a rotary evaporator, set the rotary evaporation temperature to 50°C, the rotary evaporation time to 2 h, and take out the mixed powder after the rotary evaporation is completed;
[0122] (14) Pre-calcination: The mixed powder after rotary evaporation is placed in a crucible, placed in a box furnace, and pre-calcined in an air atmosphere; the pre-calcination conditions are: from room temperature to 500°C, the heating rate is 5°C / min, the holding time is 4h, and after the program is completed, the furnace is cooled to obtain Li2TiO3 powder; the obtained Li2TiO3 powder is placed in a mortar and ground, and then passed through a 100-mesh sieve, and then dried and stored;
[0123] (2) Preparation of Li2TiO3 green billet
[0124] Weigh 0.5g of Li2TiO3 powder and put it into a dog-bone-shaped mold, place it in a tablet press, and press it into shape at a pressure of 2.88MPa for 1min. Then demold it to obtain a dog-bone-shaped Li2TiO3 green billet.
[0125] (3) preparing Li2TiO3 tritium breeder ceramics, which comprises the following sub-steps:
[0126] (31) Punching measurement: Use a punch to punch a hole with a diameter of 1 mm in the middle of both ends of the dog-bone blank. Use a vernier caliper to measure the distance between the two holes and record it. Then continue to measure the width and height of the middle position of the dog-bone blank to obtain the blank size of A5 (18.72 mm × 3.34 mm × 1.80 mm). Then calculate the blank cross-sectional area.
[0127] (32) Applying silver paste: Apply silver paste on the inner wall and surrounding of the holes at both ends of the blank to increase its conductivity;
[0128] (33) Flash burning: Use two platinum wire electrodes in a box furnace to pass through the holes at both ends of the dog bone blank and fix them, and close the furnace door; then set the program on the power interface, set the furnace temperature to 730°C, the electric field strength to 80V / cm, and the current density to 60mA / mm 2 The flash firing time was 30s, the heating rate was 6℃ / min, and the holding time was 2h. After the furnace temperature stabilized, the flash firing program was started. After the flash firing was completed, the power was turned off and the furnace was cooled to room temperature to obtain dog-bone-shaped Li2TiO3 ceramics.
[0129] The morphology and structure of the Li2TiO3 tritium breeder ceramics prepared in the above comparative examples and embodiments were analyzed:
[0130] According to the Archimedean principle, the density of Li2TiO3 ceramics was measured using a Mettler-Toledo electronic analytical balance. The densities of the Li2TiO3 ceramics prepared in Examples 1-5 of the present invention were 2.727 g / cm 3 , 2.835g / cm 3 , 2.844g / cm 3 , 2.856g / cm 3 and 2.953 g / cm 3 ; The density of Li2TiO3 ceramic in the comparative example is 2.751g / cm 3 .
[0131] The flash-sintered Li2TiO3 ceramics prepared in Example 1 of the present invention were subjected to XRD testing. The test results are as follows: Figure 2 As shown in the figure, it can be seen that the diffraction peaks in the figure all correspond to the monoclinic phase Li2TiO3 of the product, and no impurity peaks appear.
[0132] The flash-sintered Li2TiO3 ceramics prepared in the comparative example and Example 1 of the present invention were subjected to SEM testing. The test results are shown in FIG. Figure 3As shown in the figure, the box-type furnace sintered samples have larger pores and low density; while the flash-sintered samples have obvious sintering necks and significantly reduced pore sizes, indicating that flash sintering helps densify Li2TiO3 ceramics, which is also confirmed by the density test; at the same time, the cross section of Li2TiO3 ceramics has a "annual ring"-like grain boundary structure (such as Figure 4 These “annual ring”-like grain boundary structures provide a large number of nanoscale channels, which not only increase the specific surface area of the grain boundary, but also enrich the diffusion channels of tritium and improve the tritium release efficiency of the tritium breeder.
[0133] In order to study the effect of current density on the grain boundary structure of the prepared Li2TiO3 ceramics, high-magnification SEM tests were performed on the Li2TiO3 ceramics prepared at different current densities. The test results are shown in Figure 2. Figure 5 and 6 shown.
[0134] from Figure 5 The effects of current density and furnace temperature on grain boundary structure can be observed: Figure 5 As shown in (a)-(c), when the current density is 40mA / mm 2 and 60mA / mm 2 When the current density increases to 80 mA / mm, the diameters of the nanochannels at the grain boundaries are close, and the continuity of the nanochannel structure is observed at the grain boundaries of the two grains, indicating that the plastic deformation strain can be efficiently propagated along the grain boundaries during the flash burning process. 2 When the nanochannel diameter is significantly reduced, the channel density is significantly increased, which may be the result of the increase in flash power consumption, which increases the plastic deformation rate of the grain boundary and leads to serious dislocation plugging. Figure 5 (b), (d), and (e) show that as the furnace temperature increases from 630°C to 730°C, the diameter of the nanopores at the grain boundaries increases significantly. However, the power consumption decreases as the furnace temperature increases, especially for samples with furnace temperatures of 680°C and 730°C, where the power consumption increases from 170 mW / mm 3 Reduced to 150mW / mm 3 ; The reduced power consumption leads to a decrease in the plastic deformation rate, which may be the main reason for the increase in the nanochannel diameter.
[0135] Effect of current density on Li2TiO3 grain size Figure 6 (a)-(c) are shown; when the current density is 40mA / mm 2 When the current density increases to 60mA / mm 2 When the current density increases to 80 mA / mm, small grains appear around the large grains, but the overall grain size is still small, and the average grain size of the two is about 3 μm. 2When the temperature is high, the grain size grows significantly, and the average grain size is about 6 μm. In addition, the effect of furnace temperature on the grain size of Li2TiO3 is as follows Figure 6 As shown in (b), (d), and (e); as the furnace temperature increases from 630℃ to 730℃, the grain size of the sample increases slightly, and the maximum grain size is about 7μm; this shows that the increase in furnace temperature promotes grain growth. Comparing the effects of current density and furnace temperature on the grain size of Li2TiO3, the results show that the influence of current density is much greater than that of furnace temperature.
[0136] Analysis of the tritium release capacity of the Li2TiO3 tritium breeder ceramics prepared in Examples 1-5 above:
[0137] In order to further prove that the "annual ring" grain boundary structure is beneficial to the tritium release efficiency of the tritium multiplier, H2 was used as an alternative gas to study the H2 desorption behavior of Li2TiO3 ceramics after flash sintering. The experimental test process is as follows:
[0138] (1) Pretreatment: In an atmosphere of 10% H2-90% Ar (flow rate of 30 mL / min), heating from room temperature to 800°C at a heating rate of 10°C / min;
[0139] (2) Cooling treatment: Cooling to room temperature under Ar atmosphere (flow rate of 30 mL / min) at a cooling rate of 10°C / min; Adsorption: Adsorption was started at room temperature using a 10% H2-90% Ar mixed gas (mixed gas flow rate of 30 mL / min) until the baseline was stable and adsorption saturation was reached;
[0140] (3) Purging: After adsorption saturation at room temperature, purge with Ar (flow rate of 30 mL / min) until the baseline is stable; Programmed temperature desorption: In an Ar (flow rate of 30 mL / min) atmosphere, start programmed temperature increase and record data, and increase the temperature to 800 °C at a rate of 10 °C / min;
[0141] (4) End of test: Then, the temperature was lowered to room temperature in an Ar (flow rate was 30 mL / min) atmosphere, and the test was ended.
[0142] Figure 7 The H2 desorption peak area of Li2TiO3 ceramics at different flash current densities is given. Figure 7 (a)) and the H2 desorption peak area of Li2TiO3 ceramics at different flash furnace temperatures ( Figure 7 (b)); For samples prepared at different flash current densities, the greater the current density, the greater the total amount of H2 desorption from the sample, which is mainly due to the increase in the density of nanochannels at the grain boundaries; and for samples prepared at different flash furnace temperatures, the higher the furnace temperature, the greater the total amount of H2 desorption from the sample, which is mainly due to the increase in the diameter of the nanopores.
[0143] In summary, the present invention synthesizes and screens out ultrafine Li2TiO3 powder by low-temperature solid phase method, then places a dog-bone-shaped mold filled with ultrafine Li2TiO3 powder in a tablet press to press out a dog-bone-shaped Li2TiO3 blank, and finally sinters the dog-bone-shaped blank by flash firing equipment to obtain a high-tritium-releasing Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure. Compared with the traditional sintering method, the lithium volatilization caused by continuous high-temperature heating is reduced, and the high lithium density of the breeder is ensured; the present invention adopts a flash firing process to obtain a "annual ring"-shaped grain boundary structure, which increases the specific surface area of the grain boundary, enriches the diffusion channel of tritium, and improves the tritium release efficiency, and has great application prospects.
[0144] Those skilled in the art will appreciate that the embodiments herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.
Claims
1. A method for preparing a Li2TiO3 tritium breeder ceramic having a mesoporous grain boundary structure, characterized in that: include: (1) preparing Li2TiO3 powder; (2) Preparing a Li2TiO3 green billet: placing the Li2TiO3 powder in a mold, placing the mold in a tablet press, and performing compression molding, and demolding to obtain a Li2TiO3 green billet; (3) Preparation of Li2TiO3 tritium breeder ceramics: drilling holes at the middle positions of both ends of the Li2TiO3 blank, measuring the distance between the two holes and the width and height of the middle position of the Li2TiO3 blank, and calculating the cross-sectional area of the Li2TiO3 blank; Then apply silver paste on the inner wall and surrounding of the holes at both ends of the Li2TiO3 blank; Then two platinum wire electrodes in a box furnace are passed through the holes at both ends of the blank and fixed, and the furnace door is closed; The furnace temperature and flash firing parameters are set according to the distance between the two holes and the cross-sectional area of the Li2TiO3 blank. After the furnace temperature stabilizes, the Li2TiO3 blank is flash fired. After the flash firing is completed, the power is turned off and the blank is cooled with the furnace to obtain Li2TiO3 tritium breeder ceramics. The flash firing parameters include electric field strength, current density and flash firing time.
2. The method for preparing the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure according to claim 1, characterized in that: The preparation process of the Li2TiO3 powder comprises: (11) LiOH·H2O and TiO(OH)2 are placed in a ball mill containing a plurality of agate balls, and then a ball milling medium is added, and the ball mill is sealed; (12) placing the sealed ball mill jar in a planetary ball mill for ball milling to obtain a slurry; (13) subjecting the ball-milled slurry to rotary drying to obtain a mixed powder; (14) The mixed powder is placed in a crucible, placed in a box furnace, and pre-fired in an air atmosphere; and then ground and sieved to obtain Li2TiO3 powder.
3. The method for preparing the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure according to claim 2, characterized in that: In the step (11), the molar ratio of LiOH·H2O to TiO(OH)2 is 2:1; and the diameter of the agate ball is 2-5 mm.
4. The method for preparing the Li2TiO3 tritium breeder ceramic having a mesoporous grain boundary structure according to claim 2, characterized in that: In the step (13), the rotary evaporation temperature is 40-60° C., and the rotary evaporation time is 2-4 hours.
5. The method for preparing the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure according to claim 2, characterized in that: In the step (14), the pre-sintering temperature of the mixed powder is 500-600° C., and the pre-sintering time is 2-4 hours.
6. The method for preparing the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure according to claim 1, characterized in that: In the step (2), the mold is a dog-bone-shaped mold, and the obtained Li2TiO3 blank is a dog-bone-shaped blank.
7. The method for preparing the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure according to claim 1 or 6, characterized in that: In the step (2), during the compression molding process, the molding pressure is 2.5-3.5 MPa, and the holding time is 1-1.5 min.
8. The method for preparing the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure according to claim 1, characterized in that: In the step (3), the diameter of the holes punched in the middle of the two ends of the Li2TiO3 blank is 0.8-1.2 mm.
9. The method for preparing the Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure according to claim 1, characterized in that: In step (3), the furnace temperature is 600-800°C, the electric field strength is 70-100V / cm, and the current density is 40-80mA / mm 2 , the flash time is 10-30s.
10. Li2TiO3 tritium breeder ceramic with a mesoporous grain boundary structure prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for rapidly preparing spinel type Li4Ti5O12 lithium titanate material at low temperature
CN112374536A
Method for preparing Li2TiO3 tritium breeding microspheres and rich-phase structures in batches through centrifugal granulation
CN115888573A
High-density lithium titanate fine-grain ceramic rapid sintering method based on electric pulse
CN117756519A
